A Prebiotic/Anthocyanin Blend Improved Gastrointestinal Health and Impacted Skin Status in Humans (P20-016-19). (13th June 2019) - Lu, Jihong; Li, Jing; Ren, Yiping; Stevenson, Douglas; Bartlett, Mark
Abstract: Objectives: Previous studies revealed that the combination of anthocyanins and prebiotics had protective effects on gut health. In this study, we observed the response of oral consumption of a blend of prebiotics and anthocyanins (hereafter called Balance + ) on the gastrointestinal (GI) function of human volunteers. Skin status was also evaluated as a secondary indication. Methods: A total of 42 subjects (11 males and 31 females) with complaints of mild to moderate GI discomfort were recruited and provided a daily dose of 9.6 g/day of Balance + for 10 weeks. IBS-SSS and IBS-QOL questionnaires were used to evaluate GI function and quality of life of the subjects. An internally designed "Skin status questionnaire" was used to evaluate self-perception of skin conditions. Questionnaires were collected at the baseline, week-1, week-5, and week-10 after consumption. Results: A total score of GI discomfort derived from the validated GI questionnaires revealed an improvement of GI issues compared with baseline after 5 and 10 weeks consumption of Balance + in most, but not all, symptoms. For example, satisfaction of bowel movement was improved significantly at week 1, 5, and 10; frequency of abdominal pain occurrence was decreased at week 5 and 10; abdominal symptoms affecting daily life were significantly reduced at week 5 and 10. While abdominal pain was generally improved, the improvement was not statistically significant. Moreover no changes were found in abdominal distension. The survey also revealed that quality of life was improved significantly after consumption of Balance + and subjects were less concerned about psychological reactions relevant to abdominal discomfort. Interestingly, according to our questionnaire, general skin condition was also positively impacted after Balance + consumption. Subjects were asked to self-evaluate 7 general skin attributes including dry skin, dark skin or dark patches, sensitive skin, acne, coarse pores, fine wrinkles, and couperose skin. The self evaluation of such general skin conditions revealed improvement after 10 weeks consumption of Balance + . No severe adverse effects were found except for some mild abdominal response, e.g., abdominal pain and distension in 7.1% and 9.5% of individuals studied respectively. Conclusions: Balance + consumption may help regulate human GI system, help improve the self-perception of quality of life as well as skin conditions that may be relevant to GI status. Funding Sources: Nu Skin Research Funding. Supporting Tables, Images and/or Graphs: